Balancing Duty and Risk: A Critical Analysis of Frontline Medical Workers During Health Emergencies - Al Ahmari, Abdullah saeed M; Alqahtani, Awadh Salem; Asiri, Fahad Hassan; Samiti, Fatimah Abdullah Sulaiman; Alqahtani , Khaleel Ali (Journal of Ecohumanism, 2024)
Frontline medical workers are the backbone of healthcare systems, particularly during health emergencies. Their roles require balancing a strong sense of duty with the inherent personal and professional risks associated with crisis environments. This article critically examines the challenges faced by frontline medical staff, including physical risks, psychological stress, resource constraints, and ethical dilemmas. Drawing on recent health crises such as the COVID-19 pandemic, the study highlights the importance of systemic support, effective policies, and innovative strategies to mitigate risks while enabling these workers to perform their roles effectively. By analyzing case studies and global responses, this article provides actionable recommendations to enhance resilience and support systems for frontline medical workers, ensuring a sustainable healthcare workforce during emergencies.